Twelve-week sensorimotor training as a factor influencing movement patterns of canoe slalom athletes, assessed by the Functional Movement Screen - Chalubinska, D.; Truszczynska-Baszak, A.; Reszelewska, A.; Targosinski, P.; Rekowski, W. (Biomedical Human Kinetics, 2020)
Introduction: The aim of the study was to evaluate whether our own twelve-week Sensorimotor Exercise Programme (SEP) affected FMS results in canoe slalom athletes. The Functional Movement Screen (FMS) is a tool for detecting asymmetries and movement range limitations in order to prevent sport injuries. The screen evaluates mobility and stability in seven fundamental movement patterns. Material and methods: The study population consisted of 16 athletes from the Canoe Slalom National Team of Poland who competed in three sports categories: kayak single, canoe single, canoe double. The athletes, 13 men and 3 women, undertook the FMS screen twice before the starting season. Between the first and the second screen the athletes undertook a twelve-week long sensorimotor training programme. Results: The result analysis showed a statistically significant difference in FMS results. The mean FMS screen result after twelve weeks of training increased from 16.6 points to 19.6 points. Conclusions: An adequately designed SEP can lead to an improvement in athlete movement patterns. The FMS screen allows for assessment of changes in athlete movement patterns after twelve weeks of SEP training.